Study of the Effectiveness of Rainwater Harvesting in Overcoming Clean Water Scarcity - Munawir, Abdillah; Rusdiyanto, Edi; Fathar, Imam Rozali; Muna, Siti Umamah Naili (Civiliza Publishing, Indonesia., 2025)
Rainwater becomes refreshing and safe water for use in daily activities such as bathing and even for consumption through a recycling process. The aim of this study is to analyze the need for clean water, water scarcity and rainwater potential as well as analysis of rainwater utilization with rainwater processing technology. The methods used are the Wet Deposition and Wet & Dry Deposition methods with the Automatic Rain Water Sampler (ARWS). The software used for data processing in this research is Minitab version 21.1. The results of field studies based on data from the Mataram Meteorology, Climatology and Geophysics Agency for the NTB region, in the last 3 years, namely 2017, 2018 and 2019, show that the average rainfall in Mataram is 326 mm/year, which means the potential for rainwater to be reuse is huge. Strategic steps are needed to optimize rainwater potential, investment policies in appropriate infrastructure need to be improved, including rainwater collection systems, storage tanks and water treatment technology. Apart from that, the government's role is important in paying attention to legal, regulatory and environmental sustainability aspects in the development and utilization of rainwater resources so that they can be used as a basic ingredient for clean water needs.